Curriculum studies handbook--the next moment - Malewski, Erik (Studies in curriculum theory., 2009)
What comes after the reconceptualization of curriculum studies? What is the contribution of the next wave of curriculum scholars? Comprehensive and on the cutting edge, this Handbook speaks to these questions and extends the conversation on present and future directions in curriculum studies.